Spin to charge conversion in chemically deposited epitaxial La0.9MnO3 thin films capped with Pt. Issue 15 (21st March 2022) - Martin-Rio, Sergi; Pomar, Alberto; Frontera, Carlos; Wang, Hailin; Manzorro, Ramón; Magén, César; Balcells, Lluis; Mestres, Narcis; Martinez, Benjamin
Abstract : Spin-charge conversion process is studied in La0.92 MnO3 /Pt prepared by polymer-assisted deposition. Significant spin transport across the LMO/Pt interface is achieved thus, LMO could be a promising building block for all-oxide spintronics devices. Abstract : Spin to charge conversion process in a broad range of temperatures is studied in La0.92 MnO3 /Pt bilayers prepared by polymer-assisted deposition (PAD). It is shown that an excellent LMO/Pt interface can be obtained in spite of using ex situ deposition of the Pt layer. The values obtained for the effective spin-mixing conductance, g ↑↓eff = 0.76 × 10 15 cm −2, suggest that significant spin transport across the LMO/Pt interface could be achieved. Spin pumping experiments generate a transversal voltage signal V ISHE, due to spin to charge conversion via inverse spin Hall effect, that has been detected down to about 100 K with values of the spin-Hall angle, θ SH, of about 2.5%, slightly decreasing on reducing temperature in the analyzed temperature range. These results indicate that LMO is a promising perovskite building block for all-oxide multifunctional high-frequency spintronics devices and that PAD technique provides oxide epitaxial thin films of good quality adequate for spintronic applications.